Plan estratégico de marketing para la empresa procesadora y comercializadora de Arroz “Chatasqa” de la ciudad de Loja. - Sotomayor Sinche, Jack Arturo (2023)
The fundamental purpose of implementing a "Strategic Marketing Plan for Chatasqa Rice Processing and Marketing Company" lies in the conception and execution of marketing strategies to enhance the market positioning and sales of the company under study. This plan was structured around four specific objectives, starting with a comprehensive analysis of the company's situation. To achieve this, internal, external, and competitive research was conducted to identify its main strengths, opportunities, weaknesses, and threats. In the internal analysis, the EFI matrix was used as a central tool, along with interviews and direct observation. Furthermore, an external analysis was conducted, commencing with a competitive study and the application of Porter's Five Forces model to assess its level of competitiveness. The second objective focused on gathering information from the company's customers through surveys, with the purpose of discerning their preferences and tastes in relation to its primary product, rice. Throughout this research process, various strategic tools were employed, such as the Ansoff matrix and the high-impact matrix. Additionally, the SWOT matrix was used to identify key factors. In line with the third objective, micro and macro strategies based on the Marketing Mix were developed, leveraging the results obtained in the research as a reference point. Finally, the fourth objective centered on creating the budget for the marketing plan and defining the strategies to be executed, resulting in a total of $3,637.20. Additionally, the study includes conclusions drawn from the research, recommendations for the company, and the bibliography that supports the investigation.